2017
DOI: 10.1111/ans.14079
|View full text |Cite
|
Sign up to set email alerts
|

Immediate autologous breast reconstruction after neoadjuvant chemoradiotherapy for breast cancer: initial results of the first 29 patients

Abstract: Many, but not all, breast reconstructive surgeons consider autologous reconstruction as the 'gold' standard in the presence of radiotherapy. Rearranging the order of radiotherapy and surgery means operating in a recently irradiated field. We believe the surgical challenges are outweighed by a shorter and simpler reconstructive journey that additionally results in a better cosmesis. It is possible to perform immediate free autologous reconstruction after neoadjuvant chemotherapy and preoperative radiotherapy wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 30 publications
(48 reference statements)
5
9
0
Order By: Relevance
“…30 Historical concerns regarding preoperative radiotherapy include the perception of increased postoperative surgical wound complications, but several contemporary studies refute this idea. 15,17,29,31 The largest of these, a review of the American College of Surgeons National Surgical Quality Improvement Program database, assessed the impact of preoperative radiotherapy on 30-day postoperative morbidity after mastectomy with or without breast reconstruction. 31 In both the mastectomyonly and immediate reconstruction groups, preoperative radiotherapy was not associated with an increased risk of complications after multivariate regression analysis (9•4% with preoperative radiotherapy vs 11•1% without preoperative radiotherapy for mastectomy only; p=0•48; and 14•7% vs 11•2% for immediate reconstruction; p=0•22).…”
Section: Patients (N=33)mentioning
confidence: 99%
See 1 more Smart Citation
“…30 Historical concerns regarding preoperative radiotherapy include the perception of increased postoperative surgical wound complications, but several contemporary studies refute this idea. 15,17,29,31 The largest of these, a review of the American College of Surgeons National Surgical Quality Improvement Program database, assessed the impact of preoperative radiotherapy on 30-day postoperative morbidity after mastectomy with or without breast reconstruction. 31 In both the mastectomyonly and immediate reconstruction groups, preoperative radiotherapy was not associated with an increased risk of complications after multivariate regression analysis (9•4% with preoperative radiotherapy vs 11•1% without preoperative radiotherapy for mastectomy only; p=0•48; and 14•7% vs 11•2% for immediate reconstruction; p=0•22).…”
Section: Patients (N=33)mentioning
confidence: 99%
“… 14 However, there is a paucity of data on the role of preoperative radiotherapy before mastectomy and microvascular autologous reconstruction. 15 Studies reporting on the safety of preoperative radiotherapy with mastectomy and reconstruction have largely involved pedicle flaps with or without implants, 14 , 16 , 17 , 18 and only one study reported on microvascular reconstruction. 15 Of note, that study included patients with inflammatory breast cancer and skin involvement, half (49%) of whom did not have skin-sparing mastectomy, more than half (52%) had a scheduled reoperation for delayed flap inset, and not all patients received microsurgical reconstruction.…”
Section: Introductionmentioning
confidence: 99%
“…Novel approaches have been proposed for the timing of chest wall radiotherapy in high‐risk premenopausal and postmenopausal women to reduce potential morbidity associated with immediate DIEP flap reconstruction. In particular, there is no high‐quality evidence supporting NART as an alternative to PMRT in immediate autologous procedures. Using NART in women undergoing mastectomy and IBR reportedly confers potential advantages, including radiotherapy to a ‘native’ breast and the in situ index tumour that might be easier than targeting residual tissues after mastectomy and reconstruction.…”
Section: Resultsmentioning
confidence: 99%
“…The generic reference to ‘breast reconstruction’ was intended to capture all articles addressing the type and timing of breast reconstruction. Two authors independently reviewed abstracts of all studies published between 1985 and 2014, and the full texts of those studies published in 2015–2017. Levels of clinical evidence (LoE) were evaluated for each publication and scored from I to V by employing Oxford criteria.…”
Section: Methodsmentioning
confidence: 99%
“…They did find an increased risk of early complications in patients with a higher BMI (P = 0.0009). 12 Grinsell et al 13 published their series of 29 patients with LABC (including those with bony metastatic disease) treated between 2010 and 2015 with NART, with a very low rate of surgical complications (one re-operation for haematoma).…”
Section: Discussionmentioning
confidence: 99%